Internalisasi Nilai Moderasi Beragama (Adaptif terhadap Budaya Lokal) dalam Tradisi Perhitungan Weton pada Pernikahan - Anggraini, Reni Dwi; Nafiadi, Fardan Harish; Putri, Fitria Azizah Yona; Rasmuin, Rasmuin (Lembaga Yasin AlSys, 2025)
Indonesia as a country with religious diversity still upholds unity and integrity through the application of the concept of religious moderation. The view of religious moderation initiated by the Indonesian Ministry of Religious Affairs aims to maintain a balance of religious understanding so as not to be trapped in extremism, either strict or too loose. This research focuses on the tradition of weton calculation in Javanese marriage which is a form of adaptation of local culture with Islamic values, in accordance with the value of religious moderation, namely adaptive to local culture. The weton tradition is considered important in determining the good day and compatibility of the couple before the wedding takes place, and has become part of the life of Javanese people who still uphold customs. Using a descriptive qualitative approach through ethnographic methods, Plandi Village, Wonosari District, Malang Regency became the location of this research. The results show that although the weton tradition has strong cultural roots, this practice is not contrary to Islamic teachings as long as it is not considered as the only way to determine goodness. Thus, this tradition can be judged as a custom that is in line with Islamic values and contributes to the efforts of religious moderation in Indonesia.